Alcohol Prohibition and Pricing at the Pump - Kai Fischer (The Journal of Industrial Economics, 2023)
Firms often sell a transparent base product and a valuable add-on. If only some consumers are aware of the latter, the add-on's effect on the base product's price will be ambiguous. Cross-subsidization between products to bait uninformed consumers might lower, intrinsic utility from the add-on for informed consumers might raise the price. We study this trade-off in the gasoline market by exploiting an alcohol sales prohibition at stations as an exogenous shifter of add-on availability. Gasoline margins drop by 5% during the prohibition. The effect is mediated by shop variety and competition. Using traffic data, we unveil sizeable consumer-side reactions.
Keywords: 330